2012
DOI: 10.4317/medoral.17395
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mast Cells on Angiogenesis in Oral Squamous Cell Carcinoma

Abstract: Objective: Angiogenesis or neovascularization has long been known to aid in progression and metastasis of malignant tumors. Tumor angiogenesis is a complex event mediated by angiogenic factors released from cancer cells and or by host immune cells. Mast cells may induce tumor progression and potentiate metastasis by stimulating angiogenesis. The purpose of the present study was to validate topographic distribution of micro vessel density (MVD) and mast cell density (MCD) and help to elucidate the possible role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
(34 reference statements)
2
32
2
Order By: Relevance
“…Further, in this study, there was no statistically significant correlation between MCD with age, gender, and degree of tumor differentiation. In contrast, Kalra et al [18] showed that inter-comparison within the degree of differentiation with MCs count was decreased from well differentiated to poorly differentiated OSCC. The contribution of different etiological factors in the formation of OSCC in the two studies may have contributed to this difference.…”
Section: Discussionmentioning
confidence: 89%
“…Further, in this study, there was no statistically significant correlation between MCD with age, gender, and degree of tumor differentiation. In contrast, Kalra et al [18] showed that inter-comparison within the degree of differentiation with MCs count was decreased from well differentiated to poorly differentiated OSCC. The contribution of different etiological factors in the formation of OSCC in the two studies may have contributed to this difference.…”
Section: Discussionmentioning
confidence: 89%
“…First, unlike tumor cells, endothelial cells (ECs) are genomically stable, homogenous and could be ideal therapeutic targets that would not become resistant to anti-angiogenic therapy [5]. Second, turnover of tumor ECs is up to 50 times higher than that of endothelium in normal quiescent tissues [6]. Third, since anti-angiogenic therapy is directed at activated ECs, target would be easily accessible by systemic administration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Second, turnover of tumor ECs is up to 50 times higher than that of endothelium in normal quiescent tissues [6]. Third, since anti-angiogenic therapy is directed at activated ECs, target would be easily accessible by systemic administration [6]. However, different mechanisms of acquired resistance to anti-angiogenic agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mast cells exert distinct non-immunological functions, being involved in tissue homeostasis, fibrosis and angiogenesis. The involvement of mast cells in angiogenesis has been strongly supported by clinico-pathological (3)(4)(5) and experimental studies (6,7) in different malignant and non-malignant diseases, but their role in the angiogenic process is still not well characterized. The involvement of mast cells in angiogenesis is supported by the ability of these cells to secrete growth factors and molecules that induce vascular hyperpermeability (8).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of mast cells in angiogenesis is supported by the ability of these cells to secrete growth factors and molecules that induce vascular hyperpermeability (8). Convincing data supporting a role for mast cells in tumor progression via formation of new blood vessels have accumulated (3,4). Because of the lack of data concerning the use of P1.HTR cells as an experimental tool for obtaining a mastocytoma tumor model, we proposed here to study the early and late effects of the P1.HTR cell line implanted on the chick embryo chorioallantoic membrane.…”
Section: Introductionmentioning
confidence: 99%